Industry 5.0. IIoT platform as enabler for smart manufacturing - Cayuqueo, Ayelen (2024)
The work develops concepts about Industrial Internet of Things (IIoT) platforms and how this paradigm can give insights to empower industrial operation managers. The concepts are followed by an adoption case in a company in the food sector. The case give visibility to the possibilities generated by the adoption of IIoT in an industry that deliver high quality supplies to the food value chain. The article includes concepts on data integration in the industry, the IIoT architecture and its components, and the technological ecosystem that facilitates the adoption of the solution. The adoption of the IIoT platform in industrial firms occurs within the framework of the evolution towards the Industry 5.0 model. The article discusses the adoption process, the integration of different hardware and software components, according to the ISA 95 standards. In the described case, the IIoT platform is an industrial solution from Siemens that works with open components such as Node-RED or Grafana. Among the achievements achieved by the project, the fact of obtaining indicators (KPIs) that can be viewed on dashboards stands out, thus facilitating decision-making for process engineers. Finally, the article conclude on the importance of the IIoT platform to continue the evolution from descriptive analytics to prescriptive analytics.